1991
DOI: 10.1038/bjc.1991.130
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal growth factor receptors in intracranial and breast tumours: their clinical significance

Abstract: Summary A method to determine the binding of epidermal growth factor (EGF) to the particulate fraction of the cell has been established and evaluated using rat liver, human placenta, and tumours of human breast and brain. Little EGF receptor (EGFR) activity was detected in normal or benign tumour tissues except for meningioma (positive in 95% samples), but EGFR were present in 43% of 131 breast tumours and 75% of 55 primary cerebral tumours. Despite the strong inverse correlation between EGFR activity and oest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
18
0

Year Published

1992
1992
2001
2001

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 31 publications
2
18
0
Order By: Relevance
“…The present study found no evidence that EGFR measurements offer prognostic information additional to that provided by ER concentration, node status and tumour grade. These findings are also in line with our previous study (Hawkins et al, 1991) and the results of multivariate analyses by Dutch workers (Koenders et al, 1993;Foekens et al, 1989) and may perhaps relate to factors other than the four listed above. In the present study, in order to be able to include as many tumours (irrespective of size) as possible, we changed our method for EGFR assay from a multiple-dose one with Scatchard analysis (Hawkins et al, 1991) to a single saturating-dose assay.…”
Section: Resultssupporting
confidence: 92%
See 4 more Smart Citations
“…The present study found no evidence that EGFR measurements offer prognostic information additional to that provided by ER concentration, node status and tumour grade. These findings are also in line with our previous study (Hawkins et al, 1991) and the results of multivariate analyses by Dutch workers (Koenders et al, 1993;Foekens et al, 1989) and may perhaps relate to factors other than the four listed above. In the present study, in order to be able to include as many tumours (irrespective of size) as possible, we changed our method for EGFR assay from a multiple-dose one with Scatchard analysis (Hawkins et al, 1991) to a single saturating-dose assay.…”
Section: Resultssupporting
confidence: 92%
“…We have selected four putative biochemical indices of prognosis and evaluated them in a prospective study. The putative markers chosen were the oestrogen receptor (ER), the epidermal growth factor receptor (EGFR), cathepsin D (cath D) and cyclic AMP-binding protein(s) (c-AMP-b).The oestrogen receptor, a nuclear protein (Mr 66 kDa) has been shown to relate to both endocrine sensitivity (Jensen, 1975) and prognosis in multiple studies, including our own previous work (Humeniuk et al, 1982;Hawkins et al, 1987aHawkins et al, , 1991, although some consider that it is only of prognostic significance in the early years after treatment (e.g. Saez et al, 1983).…”
mentioning
confidence: 99%
See 3 more Smart Citations